Thermodynamic Modelling of Oxide Conversion Processes for Metals of Life - Mikadze, O.I.; Bagdavadze, J.I.; Dzigrashvili, T.A.; Maisuradze, N.I. (Металлофизика и новейшие технологии, 2015)
In the presented work, the environmentally friendly production processes of pure metals via reduction from the respective oxides in the atmosphere of ultra-low oxidation potential (PO₂=10¹⁶—10²⁶ atm) are offered. We propose the formation of such an environment by injection of ethyl alcohol in the reactor and interaction of its vapour with oxygen. Such conditions promote dissociation of oxides of almost any kind. Using this method, the pure, so-called ‘metals of life’ are obtained: Cu, Fe, Ni, and Co, which are used in medicine as the essential nutrients. In the case of chromium conversion, this process is completed with the synthesis of carbide phases. Production of pure Cr is possible by using the similar methodology with the help of oxygen pump. For identification of the reduced products, an X-ray phase analysis is used. The purity of the converted products is characterized by spectrochemical analysis. The experimental data are in a good conformity with the thermodynamic calculations of optimal temperature ranges of conversion reactions and the ratio of the initial ingredients.